Allium oculisandrasicum (A. sect. Codonoprasum, Amaryllidaceae), a new species from Türkiye - Eker İsmai̇l (Phytotaxa, 2025)
Allium oculisandrasicum Eker, a new species of sect. Codonoprasum, is herein described and illustrated from Denizli Province, Türkiye. The species morphologically shows certain affinities with A. phrygium Boiss. and A. ankarense Yıld., from which it differs in several diagnostic characters, particularly those related to the bulb tunics, scape, spathe valves, leaves, pedicels, inflorescence, perigone, and generative organs. Data on its morphology, ecology, distribution, conservation status, and taxonomic affinities are presented.